As empresas transnacionais como instrumento em prol do desenvolvimento econômico, social e ambiental diante do novo marco legal do saneamento básico - Bueno, Isadora Carvalho (2023)
The research project seeks to demonstrate the importance of transnational companies as a solution to basic sanitation problems in Brazil, especially after the changes resulting from the new regulatory framework for basic sanitation - Law 14.026/2020. As a way of guiding the Executive's decisions in the implementation of a public policy on basic sanitation, as well as subsidizing transnational companies with relevant legal information on the subject, when making decisions. The theme is current and relevant, since Brazil has a deficit in the sanitation sector, mainly from the point of view of water and sewage services, while the National Plan for Basic Sanitation imposes as a goal the universalization of basic sanitation services throughout the entire country. national territory until 2033, which implies large investments. In this context, this paper analyzes private transnational companies as an essential part of improving the structure of providing environmental sanitation services in the strict sense: water and sewage. By means of a deductive method, bibliographical review and analysis of concrete cases, the project identifies the problem of basic sanitation in the country and concludes that it is fully legal for the performance of transnational companies in the sector, with emphasis on the analysis of environmental sanitation as a fundamental right essential to healthy quality of life and guarantor of the fundamental objectives of the Federative Republic of Brazil, mainly national development, the eradication of poverty and marginalization and the reduction of social and regional inequalities.